2012
DOI: 10.1121/1.4726017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alcoholic intoxication on the fundamental frequency of female and male speakers

Abstract: This study investigates long-term features and utterance contours of fundamental frequency (f0) derived from the German Alcohol Language Corpus. The corpus comprises read, spontaneous, and command&control speech uttered by 148 speakers of both genders and various age groups when sober and intoxicated. f0 median, f0 range, and f0 contours are analyzed for intoxication and interactions with gender and age. Contours are compared both directly (root mean squared error, statistical correlation, or the Euclidean dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…DCT coefficients w x () with lower indices represent low-frequency movements (ripples) in the transformed waveform, while coefficients with higher indices represent ripples of high frequency. The first coefficient of the DCT, w x ( ¼ 1), is the same for all contours due to the preceding normalization and is therefore not considered in the analysis (Baumeister et al, 2012). Varying the number of lower DCT coefficients showed that ripple frequency indices 2 to 7 yielded the best distinction between intoxicated and sober RMS contours,…”
Section: Distance Measures-methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…DCT coefficients w x () with lower indices represent low-frequency movements (ripples) in the transformed waveform, while coefficients with higher indices represent ripples of high frequency. The first coefficient of the DCT, w x ( ¼ 1), is the same for all contours due to the preceding normalization and is therefore not considered in the analysis (Baumeister et al, 2012). Varying the number of lower DCT coefficients showed that ripple frequency indices 2 to 7 yielded the best distinction between intoxicated and sober RMS contours,…”
Section: Distance Measures-methodsmentioning
confidence: 98%
“…Since the average syllable number of the test sentences was 12.3 (which equals a wave length of 0.081 L), the DCT range ¼ 2…51 should roughly cover all RMS movements up to the syllable rate (Baumeister et al, 2012).…”
Section: Dct and Moments Of Dct-methodsmentioning
confidence: 99%
See 3 more Smart Citations